Overexpression of Multiple Detoxification Genes in Deltamethrin Resistant Laodelphax striatellus (Hemiptera: Delphacidae) in China - Xu, Lu; Wu, Min; Han, Zhaojun (PLOS ONE, 2013)
BackgroundThe small brown planthopper (SBPH), Laodelphax striatellus (Fallén), is one of the major rice pests in Asia and has developed resistance to multiple classes of insecticides. Understanding resistance mechanisms is essential to the management of this pest. Biochemical and molecular assays were performed in this study to systematically characterize deltamethrin resistance mechanisms with laboratory-selected resistant and susceptible strains of SBPH. Methodology/Principal FindingsDeltamethrin resistant strains of SBPH (JH-del) were derived from a field population by continuously selections (up to 30 generations) in the laboratory, while a susceptible strain (JHS) was obtained from the same population by removing insecticide pressure for 30 generations. The role of detoxification enzymes in the resistance was investigated using synergism and enzyme activity assays with strains of different resistant levels. Furthermore, 71 cytochrome P450, 93 esterases and 12 glutathione-S-transferases cDNAs were cloned based on transcriptome data of a field collected population. Semi-quantitative RT-PCR screening analysis of 176 identified detoxification genes demonstrated that multiple P450 and esterase genes were overexpressed (>2-fold) in JH-del strains (G4 and G30) when compared to that in JHS, and the results of quantitative PCR coincided with the semi-quantitative RT-PCR results. Target mutation at IIS3–IIS6 regions encoded by the voltage-gated sodium channel gene was ruled out for conferring the observed resistance. Conclusion/SignificanceAs the first attempt to discover genes potentially involved in SBPH pyrethroid resistance, this study putatively identified several candidate genes of detoxification enzymes that were significantly overexpressed in the resistant strain, which matched the synergism and enzyme activity testing. The biochemical and molecular evidences suggest that the high level pyrethroid resistance in L. striatellus could be due to enhanced detoxification rather than target insensitivity. The findings lay a solid ground for further resistance mechanism elucidation studies.